A house divided: Legislative competition and young firm survival in the United States - Raj, Manav (Strategic Management Journal, 2021)
Abstract Research Summary Features of the institutional environment influence the performance of firms. In this research, I examine how one aspect of the institutional environment, competition between parties within legislatures, relates to young firm mortality. I argue that higher legislative competition provides legislators with more power to reward favored interests and thus contributes to a competitive environment that benefits well‐connected incumbents and imposes negative consequences on young firms. Using data on state legislature composition in the United States and both an ordinary least squares and instrumental variables empirical strategy, I find that legislative competition has a positive relationship with young firm mortality and this relationship is partially mediated by incentives that favor incumbents. In doing so, I highlight that political competition can have negative consequences for some firms. Managerial Summary In this research, I examine how competition between parties within state legislatures affects the survival of young firms. I argue that higher interparty competition provides legislators with greater bargaining power to obtain policy rewards for favored constituents and that this can lead to a competitive environment that favors well‐connected incumbent firms and disadvantages younger firms. I find that interparty legislative competition has a positive relationship with young firm mortality and that this relationship is partially accounted for by the use of subsidies and incentives that favor incumbents. Through this research, I show that political competition may be harmful to some firms and highlight the importance of government institutions on firms and markets.